Clinical symptoms, biochemistry, and liver histology during the native liver period of progressive familial intrahepatic cholestasis type 2 - Hiroki Kondou; Satoshi Nakano; Tadahaya Mizuno; Kazuhiko Bessho; Yasuhiro Hasegawa; Atsuko Nakazawa; Ken Tanikawa; Yoshihiro Azuma; Tatsuya Okamoto; Ayano Inui; Kazuo Imagawa; Mureo Kasahara; et al. (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Progressive familial intrahepatic cholestasis type 2 (PFIC2) is an ultra-rare disease caused by mutations in the ABCB11 gene. This study aimed to understand the course of PFIC2 during the native liver period. Methods From November 2014 to October 2015, a survey to identify PFIC2 patients was conducted in 207 hospitals registered with the Japanese Society of Pediatric Gastroenterology, Hepatology, and Nutrition. Investigators retrospectively collected clinical data at each facility in November 2018 using pre-specified forms. Results Based on the biallelic pathogenic variants in ABCB11 and/or no hepatic immunohistochemical detection of BSEP, 14 Japanese PFIC2 patients were enrolled at seven facilities. The median follow-up was 63.2 [47.7–123.3] months. The median age of disease onset was 2.5 [1–4] months. Twelve patients underwent living donor liver transplantation (LDLT), with a median age at LDLT of 9 [4–57] months. Two other patients received sodium 4-phenylbutyrate (NaPB) therapy and survived over 60 months with the native liver. No patients received biliary diversion. The cases that resulted in LDLT had gradually deteriorated growth retardation, biochemical tests, and liver histology since the initial visit. In the other two patients, jaundice, growth retardation, and most of the biochemical tests improved after NaPB therapy was started, but pruritus and liver fibrosis did not. Conclusions Japanese PFIC2 patients had gradually worsening clinical findings since the initial visit, resulting in LDLT during infancy. NaPB therapy improved jaundice and growth retardation but was insufficient to treat pruritus and liver fibrosis.